THU0091 High multi-biomarker disease activity score is associated with high risk of radiographic progression in six studies. (15th June 2017) - Curtis, JR; Brahe, CH; Ostergaard, M; Hetland, ML; Hambardzumyan, K; Saevarsdottir, S; Wang, X; Sasso, EH; Huizinga, TW
Abstract : Background: The multi-biomarker disease activity (MBDA) test uses a validated algorithm with 12 serum protein biomarkers to assess disease activity in patients with RA. The MBDA score has previously been found to be a predictor of risk for radiographic progression (RP). Objectives: To evaluate data from six cohorts to collectively establish the relationship between the MBDA score and risk for RP. Methods: Clinical, MBDA score and radiographic data were analyzed for 6 cohorts with N>100: Leiden, SWEFOT Year 1, SWEFOT Year 2, OPERA Year 1, and AMPLE Year 1 (abatacept and adalimumab arms) (see Figure). Analyses used published results when available or patient-level data when not (i.e., for Leiden; and for OPERA CRP analyses). Frequency of RP over one year was determined by category of MBDA score (low, moderate [30–44], high on a scale of 1–100) at the start of the year for four cohorts and by category of MBDA score at the end of the year for AMPLE cohorts (as published). RP was defined using the threshold for change in total modified Sharp score (ΔmTSS) specific to each study (2 to >5 TSS units). Positive and negative predictive values (PPV and NPV) were determined for each study by comparing patients with high MBDA score (>44), DAS28-(ESR/CRP) (>5.1 or >4.09) or CRP (>3 mg/dL) vs. those in a not-high category. Relative risk (RR) for RP was determined for each study, and in a meta-analysis of the non-overlapping patient groups with MBDA scores available at the start of the year (Leiden, SWEFOT Year 1 and OPERA Year 1). Results of multivariate analyses and analyses that combined MBDA score with other risk factors for RP were summarized. Results: The 6 study cohorts included patients receiving csDMARDs alone or with adalimumab, infliximab or abatacept. Overall rates of RP were 10–26%. In each study, RP was most frequent among patients with a high vs. not-high MBDA score (>44 vs. ≤44). For high MBDA scores, NPVs were 93–97% and PPVs were 18–32%, with RR values of 3.6–9.5 (P=0.002 to <0.0001) (Figure). In a meta-analysis of the Leiden, SWEFOT Year 1 and OPERA Year 1 cohorts, RR was 5.1 (P<0.0001) for MBDA categories, and 1.4 (P=0.23) and 1.6 (P=0.01) for categories of DAS28-CRP or CRP, respectively. Previously published multivariate analyses in the Leiden and SWEFOT Year 1 cohorts showed that MBDA score was an independent predictor of RP compared with other predictors. In the Leiden cohort, MBDA score was the strongest predictor and high MBDA score discriminated between high and low risk for RP among patients with high SJC (>5) or high DAS28-CRP, with PPV as high as 57%. Conclusions: High MBDA scores were associated with increased risk for RP in 6 study cohorts, including patients treated with csDMARDs, TNFi and abatacept. Based on high NPVs (≥93%), the MBDA score used alone had clinical value for identifying patients with little or no risk of RP. Combining the MBDA score with clinical measures yielded PPVs approaching 60%, suggesting that biomarkers can help stratify patients by their risk for RP. Disclosure of Interest: J. Curtis Grant/research support from: Crescendo Bioscience Inc., Consultant for: Crescendo Bioscience Inc., C. Brahe: None declared, M. Ostergaard Grant/research support from: AbbVie, BMS, Boehringer-Ingelheim, Eli Lilly, Janssen, Merck, Pfizer, Roche, UCB, Celgene, Sanofi, Regeneron, Novartis, T Jensen, M. Hetland Grant/research support from: AbbVie, BMS, MSD, Pfizer, Crescendo Bioscience Inc., UCB, Eli Lilly, Speakers bureau: Orion, K. Hambardzumyan: None declared, S. Saevarsdottir: None declared, X. Wang Shareholder of: Myriad Genetics, Inc., Employee of: Crescendo Bioscience Inc., E. Sasso Shareholder of: Myriad Genetics, Inc., Employee of: Crescendo Bioscience Inc., T. Huizinga Consultant for: Merck, UCB, Bristol Myers Squibb, Biotest AG, Pfizer, GSK, Novartis, Roche, Sanofi-Aventis, Abbott, Crescendo Bioscience Inc., Nycomed, Boeringher, Takeda, Zydus, Epirus, Eli Lilly